Narratologiese ondersoek na Daniël 1: God beloon getrouheid - M. Nel (Acta Theologica)
The hypothesis of this article is that a narratological analysis of Daniel 1 may be useful in understanding it. Daniel 1 is a narrative without historical foundation and should be read and interpreted as literature. Whereas the tales in the Daniel book pretend to be about historical figures, they are literary tales that encourage people in a historical crisis situation. In the narratological synthesis the following elements are investigated in terms of their contribution to the tale: the narrator and his/her theological outlook; the temporal, spatial and social settings of the tale; the characters in the tale, and the plot which is a plot within a plot. The narratological discussion implies that Daniel 1 conveys the message: God is in control of what is happening with His people. His reign is sovereign. He is where His children are. His children are there because He put them there. His people have the responsibility to serve and honour Him even in the strange country of exile. He uses them in that country. and He blesses them there. He is the great God.